Deciphering Local Microstrain-Induced Optimization of Asymmetric Fe Single Atomic Sites for Efficient Oxygen Reduction - Zhang, Peng; Huang, Siying; Chen, Kuo; Liu, Xiaoqi; Xu, Yachao; Chai, Yongming; Liu, Yunqi; Pan, Yuan (Nano-Micro Letters, 2025)
Disrupting the symmetric electron distribution of porphyrin-like Fe single-atom catalysts has been considered as an effective way to harvest high intrinsic activity. Understanding the catalytic performance governed by geometric microstrains is highly desirable for further optimization of such efficient sites. Here, we decipher the crucial role of local microstrain in boosting intrinsic activity and durability of asymmetric Fe single-atom catalysts (Fe–N3S1) by replacing one N atom with S atom. The high-curvature hollow carbon nanosphere substrate introduces 1.3% local compressive strain to Fe–N bonds and 1.5% tensile strain to Fe–S bonds, downshifting the d-band center and accelerating the kinetics of *OH reduction. Consequently, highly curved Fe–N3S1 sites anchored on hollow carbon nanosphere (FeNS-HNS-20) exhibit negligible current loss, a high half-wave potential of 0.922 V vs. RHE and turnover frequency of 6.2 e−1 s−1 site−1, which are 53 mV more positive and 1.7 times that of flat Fe–N–S counterpart, respectively. More importantly, multiple operando spectroscopies monitored the dynamic optimization of strained Fe–N3S1 sites into Fe–N3 sites, further mitigating the overadsorption of *OH intermediates. This work not only sheds new light on local microstrain-induced catalytic enhancement, but also provides a plausible direction for optimizing efficient asymmetric sites via geometric configurations. Highlights: 1 Crucial role of local microstrain was deciphered to boost oxygen electrocatalysis via quantitatively riveting asymmetric Fe–N3S1 sites on carbon hollow nanospheres with specific curvature. 2 The local microstrain accelerates kinetics of *OH reduction on Fe–N3S1, enabling much enhanced intrinsic activity, selectivity and stability toward oxygen electrocatalysis. 3 The strained Fe–N3S1 sites were monitored to transformed into Fe–N3–S1 sites, further dynamically mitigating the overadsorption of *OH intermediates.